PENYIMPANGAN PRINSIP KESANTUNAN BERBAHASA MAMAH DEDEH DALAM ACARA TELEVISI MAMAH DAN AA BERAKSI - Ram, Siti Ramlah; Juita, Novia; Liusti, Siti Ainim (Universitas Negeri Padang, 2019)
This article aims to describe the type of deviations principle of language politeness and describe the cause of the principle of politeness in Mamah Dedeh. This type of research is a qualitative research that is descriptive. The instruments used in this research are researchers as primary instruments and data analysis as auxiliary instruments. Data collection techniques are done by documentation. Data wiring checks using detailed description techniques. The steps for analyzing data are collection, classification, coding and data analysis. The findings of this research are the deviations of the principle of civility Mamah Dedeh in the television show Mamah dan Aa Beraksi in Indosiar include the deviation Wisdom maxim, deviation Generosity maxim, deviation Appraisal maxim, deviations of Humility maxim, the deviation of Agreement maxim, and the deviations Sympathy maksim. The cause caused the speaker to intentionally accuse the spoken partner, speak not in context, protective of the opinions, the emotional sense, the criticism directly with the rant, mock, and give no sympathy.Keywords: language politeness, the principle of politeness, talk show